Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan - Beatus Tambaip; Paul Adryani Moento; Alexander Phuk Tjilen (Universitas Musamus, Merauke, Papua, 2023)
This This study aims to determine the participation of the community in Kampung Getentiri, Jair District, Boven Digoel Regency in Development Planning Meetings. Observational techniques, interviews, and documentation were used to collect data. The collected data was analyzed descriptively and qualitatively. The study found that although Musrembang had been conducted and generated enthusiasm among most of the community who are mostly farmers, community participation in Musrembang was still lacking. Inter-community relations were not communicative enough, and there was a lack of active involvement in providing suggestions. In terms of tokenism, the community participated in Musrembang to give their input and opinions on development plans, but the feedback provided was only formal and not followed up, giving the government greater control over development programs. This highlights the need to strengthen community participation in the planning and implementation of development, ensuring that their feedback is not merely a formality but also taken into consideration in decision-making. Furthermore, in terms of the community's power in development planning in Kampung Getentiri, the community has power in development planning. They are involved directly in the initial meetings with the village head and Musrembang and are enthusiastic about providing input. The results of Musrembang give the community authority to participate in implementing development programs, although they are still monitored by the village authorities.